The Factors Influencing the Use of Address terms in English and Gorontalese: A Sociolinguistic Analysis - Hamzah, Aryati (Eastasouth Institute, 2024)
Communication plays a vital role in human interaction, enabling the exchange of ideas, feelings, and thoughts. In conversation, address terms reflect linguistic and social dynamics, signifying relationships, social status, and cultural norms. This study contrasts the use of address terms in English and Gorontalese within sociolinguistic contexts, focusing on factors influencing their application: situational context, marital status, and emotional expression. A descriptive qualitative method with contrastive analysis was employed, drawing data from literature, Gorontalo linguistic sources, and English interactions. Findings reveal that in formal settings, Gorontalese speakers utilize titles and Indonesian language for respect, while English speakers rely on terms such as